Review of Theoretical Approaches to the Study of the Relationship between Students’ Socio-Economic Status and Educational Choice - Чиркина, Татьяна (Journal of Economic Sociology, 2018)
Major changes have happened in the Russian educational system in recent decades. The number of people who continue studying after finishing secondary school has increased significantly, as well as the number of universities and students. The key predictor of educational trajectory is the socioeconomic status (SES) of the students’ families. A lot of research has been devoted to studying family influence on educational trajectory choice. This article considers the main theoretical approaches to studying the relationship between trajectory choice and student SES in the context of higher education expansion. In addition, empirical studies are analyzed, to test the implementation of the described theories in various education systems. Macro- and micro-theories are identified to explain the reasons for the reproduction of inequality at state and individual levels respectively. Macro-theories describe conditions when inequality persists despite increasing access to education and tell us how to overcome inequalities. These theories are used for comparing students’ cohorts and identifying changes in accessibility to a certain level of education over time. Micro-theories study educational transitions at the individual level and consider the reasons for choosing a trajectory in terms of students’ opportunities, preferences, and limitations. The current review of both empirical and theoretical studies will be useful for future research in this area to make predictions and determine a valid model of the relationship between SES and the choice of educational trajectory in Russia